Interdisciplinary concepts in cardiovascular health : Volume I: Primary Risk Factors - Groschner, Klaus; Wakabayashi, Ichiro (Springer Vienna, 2013)
This book provides an introduction to the principles of both cardiovascular epidemiology and molecular pathophysiology; as a unique aspect, it also outlines and discusses the molecular concepts underlying epidemiological observations. This first volume is focused on the genetic and molecular basis of pathogenesis and the role of environmental factors triggering cardiovascular dysfunctions. The book promotes the use of interdisciplinary approaches in the field of preventive medicine based on recent advances in molecular and cellular pathophysiology. The book offers a valuable resource work for researchers in basic biomedical fields and clinical scientists alike, as well as guidelines for novel avenues of research in both basic pathophysiology and cardiovascular therapy and prevention.